Implementasi Nilai Tabligh Pada Tenaga Pengajar Dalam Proses Belajar Mengajar di Madrasah Aliyah Negeri Mojokerto - Amalia, Iffa; Herianingrum, Sri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Islam teaches every human being which have been blessed by Allah SWT with variousÂ advantages to be thankful for what they have by utilizing his/her ability through dig andÂ developing his/her potential in a good way, so that it can be meaningful for him/herself asÂ well as to other people. The teachers at school, which has been trusted by other parties toÂ constantly, transfers his/her knowledge and conduct their pupil according to theÂ characteristics of Rasulullah SAW so that theyâre able to reach success in that school, and ofÂ the characteristic is tabligh. The outcome of this research is, teachers have implementedÂ tabligh on the teaching âlearning process communicatively, it was proofed by the fulfillmentÂ of 5 indicators which are; communication, model, education, wisdom and firmness whichÂ caused the escalation of studentâs morality until today. The teachers which haveÂ implemented tabligh are able to create a pleasant and conducive class with Islamic ethics.Â The implementation of tabligh is able to create excellent and high quality human resources.The excellent and high quality human resources will be able to build his/her economiccondition as well as build the nationâs.